Adult Stem Cell Therapies for Wound Healing: Biomaterials and Computational Models - Tartarini, Daniele; Mele, Elisa (Frontiers in Bioengineering and Biotechnology, 2016)
The increased incidence of diabetes and tumors, associated with global demographic issues (aging and life styles), has pointed out the importance to develop new strategies for the effective management of skin wounds. Individuals affected by these diseases are in fact highly exposed to the risk of delayed healing of the injured tissue that typically leads to a pathological inflammatory state and consequently to chronic wounds. Therapies based on stem cells have been proposed for the treatment of these wounds, thanks to the ability of stem cells to self-renew and specifically differentiate in response to the target bimolecular environment. Here we discuss how advanced biomedical devices can be developed by combining stem cells with properly engineered biomaterials and computational models. Examples include composite skin substitutes and bioactive dressings with controlled porosity and surface topography for controlling the infiltration and differentiation of the cells. In this scenario, mathematical frameworks for the simulation of cell population growth can provide support for the design of bio-constructs, reducing the need of expensive, time-consuming and ethically controversial animal experimentation.